Winter story - Barklem, Jill (Barklem, Jill. Brambly Hedge., 2017)
As an unusually severe winter blankets Brambly Hedge with more snow than even old Mrs. Eyebright can ever remember, the tiny community of field mice makes plans to hold a giant Snow Ball festival.